132 Conflict resolution: protocol for an experimental study of users' perceptions and responses to competing interest disclosure statements in patient decision aids. (20th August 2018) - Thompson, Rachel; Stevens, Gabrielle; Washburn, Hillary; Barr, Paul
Abstract : Background: Competing interests among patient decision aid authors have potential to undermine the usefulness of these tools for supporting patients to make informed and values-concordant health decisions. Competing interests may also contribute to overdiagnosis and overtreatment. Prevailing decision aid quality standards attempt to counteract the potential effects of competing interests by advocating disclosure. However, we know little about how decision aid users perceive and respond to competing interest disclosure statements and thus, whether this approach is sufficient. This poster will describe the protocol for a forthcoming experimental study designed to better understand users' perceptions of and reactions to competing interest disclosure statements in patient decision aids. Methods: Approximately 360 English-speaking adults in the United States will be recruited to participate in an online survey using a commercial panel service. Recruitment quotas will be imposed so that the final sample is composed equally of participants with adequate and limited health literacy. During the survey, participants will be asked to ' Imagine that you have been told by a doctor that you have a rare and serious strain of the flu called Elephant Influenza ' and will be randomised to receive advice that either ' While searching online, you find this decision aid on treatment options for Elephant Influenza ' or ' While in the clinic, your doctor gives you this decision aid on treatment options for Elephant Influenza '. Participants will then be randomised to view a brief fictional patient decision aid on treatment options for Elephant Influenza that features one of three different competing interest disclosure statements (disclosure of no competing interests, disclosure of competing interests, disclosure of competing interests with additional cautionary statement about the bias competing interests can introduce) and asked several closed and open-ended questions. Analysis and dissemination: Data analysis will address four primary research questions: (1) how frequently do decision aid readers notice, remember, and understand author competing interest disclosure statements in a patient decision aid, and does this depend on type of disclosure statement? (2) what is the effect of type of disclosure statement on decision aid readers' perceptions of the trustworthiness of the decision aid, their (hypothetical) treatment choices, and their perceptions of the values concordance of their (hypothetical) treatment choices? (3) is the effect of type of disclosure statement on perceived trustworthiness, treatment choices, and perceived values concordance moderated by the (imagined) mode of delivery of the decision aid? and (4) how unnecessary, informative, patronizing, and important do decision aid readers perceive disclosure statements to be, and does this depend on type of disclosure statement? Study results will be disseminated widely and inform understanding of the adequacy of current approaches to managing competing interests among patient decision aid authors.